2008
DOI: 10.1080/00032710701792737
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Polymer–Carbon Nanotube Composite Materials and Their Applications for Enzyme Entrapment

Abstract: Carbon Nanotubes (CNTs), single-, double-, and multiwalled can be easily suspended up to 10 mg/ml in biocompatible carboxymethylcellulose or k-carrageenan as these polymers are envisioned to wrap themselves around CNTs effectively forming aqueous solutions. Glucose oxidase was used as a model to show the biocompatibility and stability of the entrapped enzyme in a k-carrageenan-CNT network.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…However, SWCNTs exhibit more distinctive electrical and optical properties when compared to MWCNTs. On the other hand, MWCNTs show more chemical resistance than SWCNTs [4]. This characteristic is of significant importance when functionalization is required which means the surface structure of pristine CNTs is modified by chemical methods to meet the requirements of desired specific application.…”
Section: Introductionmentioning
confidence: 99%
“…However, SWCNTs exhibit more distinctive electrical and optical properties when compared to MWCNTs. On the other hand, MWCNTs show more chemical resistance than SWCNTs [4]. This characteristic is of significant importance when functionalization is required which means the surface structure of pristine CNTs is modified by chemical methods to meet the requirements of desired specific application.…”
Section: Introductionmentioning
confidence: 99%
“…46 One study has shown a similar effect in weakly acidic solutions with pristine kappa-carrageenan hydrolyzing to poligeenan. 47 Despite this loss in conductivity over storage, dopamine oxidation proceeded similarly in both new and 3-month old solutions of GO:KC. Upon the addition of 5.75 μM DA, an oxidation peak of 0.23 V and 0.22 V for the bare GCE and film-modified electrode were observed respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Carbon nanotypes have various features such as nanoendurance morphology, high resistance, suitable surface to increase the ratio of the electric and magnetic properties (electrical permeability factor), and high permittivity . Single‐walled nanotubes have less strength than multiwalled nanotubes . One of their most important features is their functioned surface that makes them very suitable for the sensor .…”
Section: Introductionmentioning
confidence: 99%